2018
DOI: 10.1007/s10086-018-1773-1
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of volatile compounds from five interior decoration timbers in Taiwan using TD/GC–MS/FID

Abstract: Volatile organic compounds (VOCs) released from Chamaecyparis formosensis, Cryptomeria japonica, Cunninghamia lanceolata, Chamaecyparis obtusa var. formosana, and Taiwania cryptomerioides five major building and interior decoration timbers and their essential oil components were analyzed using GC-MS and TD/GC-MS/FID. Results showed that C. obtusa var. formosana had the highest yield of essential oil (3.42%), followed by C. formosensis (3.14%), while C. japonica had the lowest yield (0.95%). Moreover, oxygenate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Aromatic plants, such as C. japonica, synthesized and emitted complex mixtures of volatile organic compounds (VOCs) in order to facilitate their growth and survival [13,65].…”
Section: Pharmacological Properties Of C Japonica Eomentioning
confidence: 99%
See 1 more Smart Citation
“…Aromatic plants, such as C. japonica, synthesized and emitted complex mixtures of volatile organic compounds (VOCs) in order to facilitate their growth and survival [13,65].…”
Section: Pharmacological Properties Of C Japonica Eomentioning
confidence: 99%
“…These VOCs were assessed as having soothing effects in a human sensory evaluation [68]. Moreover, the main constituent of C. japonica heartwood EO is δ-cadinene [10,13]. It is believed that this compound and other VOCs of C. japonica suppress the sympathetic nervous system activity in humans, especially in women, stimulating relaxing and pleasurable emotions [69].…”
Section: Pharmacological Properties Of C Japonica Eomentioning
confidence: 99%
“…Pinenes are major volatile terpenoids in T. cryptomerioides, and in addition to α-pinene and α-pinene/terpinolene synthase, we functionally characterized a β-pinene synthase (TcTPS16) in this study, which allowed us to explore pinene biosynthesis in T. cryptomerioides (Figure 6) [7,9,11]. In TcPinS and TcTeoS mutagenesis studies, the slight exchange of residue would result in the ratio of monocyclic and bicyclic products [21].…”
Section: Characterized Monoterpene Biosynthetic Pathway In Taiwania Cryptomerioidesmentioning
confidence: 99%
“…Previous studies have reported that terpenoids isolated from T. cryptomerioides have great bioactivity, such as antifungal, antimite, and antioxidation activities, and most of them are sesquiterpenoids and diterpenoids, which are extracted from wood [3][4][5][6]. However, the needles of T. cryptomerioides contained high amounts of acrylic and cyclic monoterpenoids, such as limonene, pinenes, terpinolenes, and some of their derivatives [7][8][9][10][11][12], but their biosynthesis remained ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…10 Previous studies have reported the composition and antifungal activities of wood of C. lanceolata. [11][12][13][14][15][16][17] However, only 1 report noted the composition of leaf essential oil, but this report did not evaluate the biological activity. 11 No prior study has investigated the chemical composition and biological activity of the cones essential oil.…”
mentioning
confidence: 99%